Religious Tolerance Education During the Covid-19 Pandemic at SDN 04 Purwodadi - Hudhoifah, Yuyun; Raharjo, Raharjo; Ikhrom, Ikhrom (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2024)
This research was conducted to reveal how religious tolerance education in SDN. 04 Purwodadi. The data was taken using a phenomenological approach, namely revealing data on social phenomena collected by in-depth interviews. The data analysis technique used an analysis that was carried out simultaneously with the data collection process in the form of interviews with the Principal and Religious Teachers at SDN.04 Purwodadi. The results of the study found that: (1)Religious tolerance education in SDN. 04 Purwodadi is carried out thoroughly which is contained in the curriculum of the education unit, SOP for School Culture and strengthened in the curriculum of Islamic Religious Education & Budi Pekerti knowledge of religious tolerance material (moral knowing) in grade VI SD/MI (2) Religious tolerance education from the age of children is deemed necessary because it will raise awareness and strong feelings so as to motivate students to take actions of religious tolerance so that they can maintain harmony in the midst of existing community differences. (3) Religious tolerance education in Islamic religious education during the COVID-19 pandemic with the implementation of online learning should not be an obstacle. Religious tolerance education during the pandemic using social media can be an alternative learning. Because in fact, there has been a shift in people's social behavior Through social media, it is easier for people to stay in touch and communicate and interact with each other